The Influence of Innovation and Entrepreneurial Self-Efficacy to Digital Startup Success - Dessyana, Agnes; Riyanti, Benedicta Prihatin Dwi (Universitas Prasetiya Mulya, 2017)
Establishing and developing a startup business is not easy. Startup success depend on various aspects, such as financial, business model, and learning organizations. Personalities factor of founders have a contribution in business development, especially entrepreneurial self-efficacy (ESE) and innovation. But, in Indonesia, there is still no psychological study who see the contribution of those factors on business success in digital startup. This study aimed to understand how both factors influence startup digital. The sample is 64 founders. The research instrument is ESE, KAI, and Business Success questionnaire (Kirton in Riyanti, 2003; Chen et al, 1998; Kaplan & Norton, 2006). Multiple-regression analyses reveal ESE and innovation contributes 20.8% to business success. ESE regression coefficient is 0.200 (P <0.05) and innovation 0.026 (p> 0.05). This means, ESE has significant positive effect, while innovation has a positive relationship but insignificant. Interventions in the form of booklets that inform how to increase ESE. The booklet is already conducted trials on five founders.